2015
DOI: 10.1017/s2040174415001154
|View full text |Cite
|
Sign up to set email alerts
|

The placental mTOR-pathway: correlation with early growth trajectories following intrauterine growth restriction?

Abstract: Idiopathic intrauterine growth restriction (IUGR) is a result of impaired placental nutrient supply. Newborns with IUGR exhibiting postnatal catch-up growth are of higher risk for cardiovascular and metabolic co-morbidities in adult life. Mammalian target of rapamycin (mTOR) was recently shown to function as a placental nutrient sensor. Thus, we determined possible correlations of members of the placental mTOR signaling cascade with auxologic parameters of postnatal growth. The protein expression and activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…mTOR can also affect the fetal growth through the regulation of placental development and function (13). Studies suggested that the placental mTOR is upregulated in pregnancies complicated by GDM, and mTOR overactivation is linked to fetal macrosomia (14,15).…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…mTOR can also affect the fetal growth through the regulation of placental development and function (13). Studies suggested that the placental mTOR is upregulated in pregnancies complicated by GDM, and mTOR overactivation is linked to fetal macrosomia (14,15).…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…In addition to the well-known role of mTOR modulating placental nutrient transport and mitochondrial respiration and thereby regulating fetal growth (Kavitha et al, 2014), a recent study in which rapamycin was given to rats during late pregnancy has shown that mTOR signaling is involved in the programming of heart defects in the offspring (Hennig et al, 2017). Moreover, placental mTOR signaling activity in IUGR correlates with growth during the first year of life (Fahlbusch et al, 2015). Therefore, mTOR signaling appears to play an important role in determining growth and survival from early pregnancy to the postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest impaired mTOR signaling may directly or indirectly disrupt placental cell growth pathways. Interestingly, placental mTOR protein levels have been correlated with early catch-up growth following FGR [21], which in turn may link mTOR-associated FGR to adverse metabolic outcomes, such as obesity, in childhood and beyond. Direct genetic deletion of mTOR from the placental trophoblasts of mice conferred a significant reduction in newborn body weight that manifested in sexually dimorphic outcomes in insulin resistance and obesity in the adult offspring [18].…”
Section: Placental Mtormentioning
confidence: 99%